L’épidémie d’Ebola en Afrique de l’Ouest - Serge Loungou (L'Espace Politique, 2017)
This article highlights three aspects related to the disease caused by the Ebola virus, which was recently declared in West Africa. It describes the statistical and spatial evolution of the infection; measures defined at the sub-regional scale and by the international community to prevent the spread of the epidemic beyond its original source; and the political and economic impact of these containment measures in the three countries most affected by the epidemic.